2017
DOI: 10.1186/s40478-017-0449-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel antibody to define histone 3.3 G34R mutant brain tumours

Abstract: Missense somatic mutations affecting histone H3.1 and H3.3 proteins are now accepted as the hallmark of paediatric diffuse intrinsic pontine gliomas (DIPG), non-brain stem paediatric high grade gliomas (pHGG) as well as a subset of adult glioblastoma multiforme (GBM). Different mutations give rise to one of three amino acid substitutions at two critical positions within the histone tails, K27M, G34R/V. Several studies have highlighted gene expression and epigenetic changes associated with histone H3 mutations;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 15 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…However this technology requires resources not accessible on a global scale. Likewise, GBM_ G34 and EPN_RELA are readily diagnosed by methylation analysis, however, both entities can be identified recently by targeting the H3.3 G34 mutation or by employing p65-RelA antibodies [9,21]. In contrast, the unequivocal recognition of GBM_MYCN with non-molecular methods still poses challenges.…”
Section: Discussionmentioning
confidence: 99%
“…However this technology requires resources not accessible on a global scale. Likewise, GBM_ G34 and EPN_RELA are readily diagnosed by methylation analysis, however, both entities can be identified recently by targeting the H3.3 G34 mutation or by employing p65-RelA antibodies [9,21]. In contrast, the unequivocal recognition of GBM_MYCN with non-molecular methods still poses challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The use of immunostaining against IDH1-R132H antibody is widely accepted and applied [13]. Haque et al [14] discovered that immunostaining for H3.3 G34R/V-mutant in glioma is also highly concordant with the genotype analysis. Our cases confirmed that the use of immunohistochemistry staining to detect H3.3 G34R-mutations is more efficient, compared Positive cutoff values of ATRX and p53 were 10% nuclear staining.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…For hemispheric tumors, immunostains for H3.3 p.G34R and H3.3 p.G34V are available; however sequencing is more specific. 54…”
Section: Pediatric High-grade Gliomas (Phgg)mentioning
confidence: 99%